PERFORMANCE ANALYSIS OF OIL AND WATER PRODUCTION IN FIELD X USING DIAGNOSTIC PLOT - Rizki Nabila; Mohammad Wildan A; Ajeng Purna Putra Oktaviani Putra Oktaviani (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2021)
Production wells have to be evaluated periodically, one of the problems that can occur is early water problems. Using X-Plot, Chan’s Diagnostic Plot, Decline Curve Analysis and Hall Plot analysis be able to detect RN-01 and RN-02 wells experienced multilayer channeling and RN-03 experienced normal displacement with high WOR.